Moral imperialism and multi-centric clinical trials in peripheral countries Imperialismo moral e ensaios clínicos multicêntricos em países periféricos - Volnei Garrafa; Claudio Lorenzo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Moral imperialism is expressed in attempts to impose moral standards from one particular culture, geopolitical region or culture onto other cultures, regions or countries. Examples of Direct Moral Imperialism can be seen in various recurrent events involving multi-centric clinical trials promoted by developed (central) countries in poor and developing (peripheral) countries, particularly projects related to the theory of double standards in research. After the WMA General Assembly refused to change the Helsinki Declaration - which would have given moral recognition to the above mentioned theory - the USA abandoned the declaration and began to promote regional seminars in peripheral countries with the aim of "training" researchers on ethical perspectives that reflect America's best interests. Individuals who received such training became transmitters of these central countries' ideas across the peripheral countries, representing a form of Indirect Moral Imperialism. The paper proposes the establishment of regulatory and social control systems for clinical trials implemented in peripheral countries, through the formulation of ethical norms that reflect the specific contexts of these countries, along with the drawing up and validation of their own national norms. Imperialismo moral é a intenção de impor padrões morais de determinadas culturas, regiões geopolíticas e países a outras culturas, regiões ou países. O Imperialismo Moral Direto pode ser exemplificado com diversos episódios recorrentes de ensaios clínicos multicêntricos promovidos por países desenvolvidos (centrais) em países pobres e em desenvolvimento (periféricos), especialmente projetos relacionados com a teoria do "double standard" de pesquisas. Com a recusa da Assembléia Geral da Associação Médica Mundial em alterar a Declaração de Helsinki, que significaria o reconhecimento moral da referida teoria, os Estados Unidos abandonaram a declaração, passando a promover seminários regionais em países periféricos com objetivo de "treinar" investigadores nas visões éticas dos interesses estadunidenses. Estes passam a ser duplicadores das idéias centrais, em diferentes instâncias das nações periféricas, caracterizando uma forma de Imperialismo Moral Indireto. O estudo propõe a construção de sistemas de regulação e de controle social para os ensaios clínicos a serem implementados nos países periféricos, por meio da formulação de normas éticas adequadas às características contextuais destes países, conjuntamente com a criação e validação de documentos normativos nacionais próprios.